2008
DOI: 10.1158/1055-9965.epi-08-0235
|View full text |Cite
|
Sign up to set email alerts
|

Target Sequence Polymorphism of Human Manganese Superoxide Dismutase Gene and Its Association with Cancer Risk: A Review

Abstract: In normal state of a cell, endogenous antioxidant enzyme system maintains the level of reactive oxygen species generated by mitochondrial respiratory chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 49 publications
5
60
0
Order By: Relevance
“…The 47cytosine-to-thymine (47C!T) transition at codon 16 in the SOD2 gene (reference SNP 4880 [rs4880]) creates a sense mutation of alanine (Ala)-tovaline (Val) in the SOD2 protein, which affects protein folding and localization. 6 Miscoding of Ala to Val in SOD2 will result in SOD2 arresting in the inner mitochondrial membrane but not in the mitochondrial matrix, therefore reducing its functional activities. 6 Carriage of 1 or 2 Ala-SOD2 allele(s) reportedly has been associated with greater risks of hepatocellular carcinoma, 7 gastric cancer, 8 prostate cancer 9 and a poor prognosis in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 47cytosine-to-thymine (47C!T) transition at codon 16 in the SOD2 gene (reference SNP 4880 [rs4880]) creates a sense mutation of alanine (Ala)-tovaline (Val) in the SOD2 protein, which affects protein folding and localization. 6 Miscoding of Ala to Val in SOD2 will result in SOD2 arresting in the inner mitochondrial membrane but not in the mitochondrial matrix, therefore reducing its functional activities. 6 Carriage of 1 or 2 Ala-SOD2 allele(s) reportedly has been associated with greater risks of hepatocellular carcinoma, 7 gastric cancer, 8 prostate cancer 9 and a poor prognosis in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…6 Miscoding of Ala to Val in SOD2 will result in SOD2 arresting in the inner mitochondrial membrane but not in the mitochondrial matrix, therefore reducing its functional activities. 6 Carriage of 1 or 2 Ala-SOD2 allele(s) reportedly has been associated with greater risks of hepatocellular carcinoma, 7 gastric cancer, 8 prostate cancer 9 and a poor prognosis in breast cancer. 10 The SNP in the GSTP1 gene (rs1695) is a substitution of A (isoleucine [Iso]) to G (valine [Val]) at position 105 that results in miscoded GSTP1 protein with decreased enzymatic activity and less effective detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms underlying these associations are uncertain, chronic inflammation is known to induce oxidant-generating enzymes and the subsequent production of reactive oxygen and nitrogen species (ROS and RNS) [9]. Furthermore, endogenous antioxidant enzymes, such as, manganese superoxide dismutase (MnSOD), and antioxidants, such as, carotenoids and tocopherols are known to play significantly roles in cellular defense against oxidative stress [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been reported that the cytosolic stress-inducible hsp70, a molecular chaperone, associates with SOD2 after synthesis and that the chaperone maintains the enzyme in an import-competent, unfolded conformation in an ATP-dependent manner (3)(4)(5)(6)(7)(8). Mice homozygous for hsp70 gene disruption exhibit a marked reduction in SOD2 activity, providing in vivo evidence for the role of hsp70 in regulating SOD2 (9).…”
mentioning
confidence: 99%